HPLC-ESI-MS/MS profiling of polyphenolics of a leaf extract from Alpinia zerumbet (Zingiberaceae) and its anti-inflammatory, anti-nociceptive, and antipyretic activities in vivo - Ghareeb, Mosad Ahmed; Sobeh, Mansour; Wink, Michael (Molecules, 2018)
Reactive oxygen species (ROS) have been linked to several health conditions, among them inflammation. Natural antioxidants may attenuate this damage. Our study aimed to investigate the chemical composition of a methanol leaf extract from Alpinia zerumbet and its possible antioxidant, anti-inflammatory, anti-nociceptive, and antipyretic effects. Altogether, 37 compounds, representing benzoic and cinnamic acid derivatives and flavonoids (aglycones and glycosides), were characterized. The extract showed substantial in vitro antioxidant effects, and inhibited both cyclooxygenase 1 (COX-1) and cyclooxygenase 2 (COX-2) in vitro, with a higher selectivity towards COX-2. It also inhibited 5-lipoxygenase (LOX) activity in vitro with nearly double the potency of zileuton, a reference 5-lipoxygenase (LOX) inhibitor. The extract exhibited anti-inflammatory effects against carrageenan-induced rat hind paw edema, and suppressed leukocyte infiltration into the peritoneal cavity in carrageenan-treated mice. Furthermore, it possessed antipyretic effects against fever induced by subcutaneous injection of Brewer’s yeast in mice. Additionally, the extract demonstrated both central and peripheral anti-nociceptive effects in mice, as manifested by a decrease in the count of writhing, induced with acetic acid and an increase in the latency time in the hot plate test. These findings suggest that the leaf extract from Alpinia zerumbet could be a candidate for the development of a drug to treat inflammation and ROS related disorders.
Gesehen am 14.12.2018